Clinical and laboratory evaluation of dimethyl sulfoxide dentin pretreatments - Ismail, Omar Abdelaziz (fi=Turun yliopisto|en=University of Turku|, 2026)
The durability of the resin-dentin bond is a critical challenge in adhesive dentistry because of the vulnerability of the hybrid layer to hydrolytic and enzymatic degradation. Several laboratory strategies have been proposed to stabilize the adhesive interface. However, many are technique-sensitive and very difficult to implement clinically. Dimethyl sulfoxide (DMSO) has been suggested as a simple adjunct capable of improving resin infiltration and bond stability due to its amphiphilic properties and ability to inhibit dentin proteases. The aim of this thesis was to evaluate the effect of DMSO dentin pretreatment on the durability of bonding resin to dentin in both in vitro and clinical situations. Laboratory studies evaluated the effect of different DMSO concentrations (5% and 50%) and application times (20 s and 60 s) under dry-bonding conditions. Microtensile bond strength, nanoleakage, and hybrid layer micromorphological characterization were analyzed after short- and long-term storage. Furthermore, two randomized controlled clinical trials (RCTs) were also performed. The first RCT was designed to evaluate DMSO pretreatment in non-carious cervical lesions (NCCLs), while the second one evaluated the same parameters in carious cervical lesions (CCLs). FDI criteria for evaluation of the restoration were assessed in different follow-ups, at baseline, 12, 24, and 36 months. The in vitro results revealed that both 5% and 50% DMSO pretreatments preserved bond strength over time and reduced nanoleakage compared with the untreated control. Application time was critical, as 60 s of pretreatment produced a more durable adhesive with a thicker, continuous hybrid layer. Clinically, DMSO pretreatment improved restoration survival rate and marginal quality. In NCCLs, pretreatment reduced marginal staining and deterioration over time, while in CCLs, survival was significantly higher (89%) compared with controls (65%) after 36 months. Within the limitations of this thesis, it could be concluded that DMSO pretreatment improves resin-dentin bond durability and clinical performance. This research represents a promising and clinically feasible strategy for adhesive dentistry.

Dimetyylisulfoksididentiinin esikäsittelyjen kliininen ja laboratorioarviointi Hampaan dentiinin ja yhdistelmämuovin välisen sidoksen kestävyys on edelleen merkittävä haaste korjaavassa hammashoidossa, sillä hybridikerros on altis hydroyyttiselle ja entsymaattiselle hajoamiselle. Useita laboratoriomenetelmiä on ehdotettu hybridikerroksen stabiloimiseksi, mutta monet niistä ovat tekniikkaherkkiä ja vaikeasti sovellettavissa kliinisesti. Dimetyylisulfoksidia (DMSO) on esitetty yksinkertaiseksi lisämenetelmäksi sen amfifiilisten ominaisuuksien ja kyvyn estää dentiinin proteaaseja ansiosta, joka voi parantaa sidosaineiden infiltraatiota ja sidoksen pysyvyyttä. Tämän väitöskirjan tarkoituksena oli tutkia DMSO-esikäsittelyn vaikutusta dentiiniin sidoksen kestävyyteen sekä in vitro -olosuhteissa että kliinisissä tutkimuksissa. Laboratoriokokeissa arvioitiin eri pitoisuuksien (5 % ja 50 %) ja esikäsittelyajan (20 s ja 60 s) merkitystä kuivissa sidostusolosuhteissa. Mikroveto lujuus, nanovuoto ja hybridikerroksen morfologia analysoitiin sekä lyhyen että pitkän säilytyksen jälkeen. Lisäksi toteutettiin kaksi satunnaistettua kontrolloitua kliinistä tutkimusta. Ensimmäisessä arvioitiin DMSO-esikäsittelyä ei-karioitumattomissa hammaskaulan vaurioissa (NCCL) ja toisessa karioituneissa hammaskaulan vaurioissa (CCL). Potilaita seurattiin 12, 24 ja 36 kuukauden ajan Maailman Hammaslääkäriliiton (FDI) kriteerien mukaisesti. In vitro -tulokset osoittivat, että sekä 5 % että 50 % DMSO-esikäsittely säilyttivät sidoksen lujuuden ja vähensivät nanovuotoa verrattuna käsittelemättömään kuivaan sidostukseen. Esikäsittelyaika oli kriittinen: 60 s esikäsittely tuotti kestävämmän sidoksen ja paksummat, yhtenäiset hybridikerrokset. Kliinisissä tutkimuksissa DMSO paransi restauraatioiden selviytymistä ja sauman laatua. NCCL-vaurioissa DMSO vähensi sauman värjäytymistä ja hajoamista ajan myötä, kun taas CCL-vaurioissa restauraatioiden selviytyminen oli merkittävästi parempi (89 %) verrattuna kontrolliryhmään (65 %) 36 kuukauden jälkeen. Tutkimuksen rajoituksista huolimatta DMSO-esikäsittely paransi resiini– dentiini-sidoksen kestävyyttä ja kliinistä toimivuutta. DMSO-esikäsittely on lupaava sekä kliinisesti käyttökelpoinen menetelmä korjaavaan hammashoitoon.